Transcriptome analysis of two tobacco varieties with contrast resistance to Meloidogyne incognita in response to PVY MSNR infection - Xu, Shixiao; Tian, Pei; Jiang, Zhimin; Chen, Xiaoxiang; Li, Bo; Sun, Jutao; Zhang, Zhiqiang (Frontiers in Plant Science, 2023)
Root-knot nematode (RKN) disease is a major disease of tobacco worldwide, which seriously hinders the improvement of tobacco yield and quality. Obvious veinal necrosis-hypersensitive responses are observed only in RKN-resistant lines infected by Potyvirus Y (PVY) M S N R , making this an effective approach to screen for RKN-resistant tobacco. To gain insight into the transcription dynamics of tobacco responses to PVY M S N R , we conducted RNA-seq analysis of the gene expression difference between infected G28 (RKN-resistant) and CBH (RKN-susceptible) varieties. A total of 7900, 10576, 9921, 11530 and 12531 differentially expressed genes (DEGs) were identified between the two varieties at 0, 1, 3, 5, and 7 d after infection, respectively. Functional enrichment analysis revealed that DEGs were associated with plant hormone signal transduction, starch and sucrose metabolism, phenylpropanoid biosynthesis, and photosynthesis-related metabolic pathways.Additional DEGs related to starch and sucrose metabolism, energy production, and the indole-3-acetic acid signaling pathway were induced in CBH plants after infection.DEGs related to phenylpropanoid biosynthesis, abscisic acid, salicylic acid, brassinosteroids, and jasmonic acid signaling pathway were induced in G28 after infection. Our findings reveal DEGs that may contribute to differences in PVY M S N R resistance among tobacco varieties. These results help us to understand the differences in transcriptional dynamics and metabolic processes between RKN-resistant and RKN-susceptible varieties involved in tobacco-PVY M S N R interaction.